PENGARUH TAX AVOIDANCE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN CONSUMER NON CYCLICALS SUB-SEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA (2019 – 2021) - Kurniawan, Handi; Rahayu, Puji; Isnaniati, Siti (Jurnal Ilmiah Cendekia Akuntansi; Vol 9 No 3 (2024): JuliDO - 10.32503/cendekiaakuntansi.v9i3.5534, 2024)
This study aims to examine and analyze the effect of tax avoidance as measured by the Effective Tax Rate (ETR) and Book Tax Difference (BDT) on firm value as measured by Price Book Value (PBV). food and beverage sector listed on the Indonesia Stock Exchange (2019-2021). The sample used in this study was taken using purposive sampling method. The sample in this study is 21 companies that have been selected from a population of 62 companies in the consumer non-cyclicals sector of the food and beverage sub-sector listed on the Indonesia Stock Exchange (2019-2021). This study uses data analysis techniques, namely descriptive statistical test, multiple linear regression analysis, classical assumption test and hypothesis testing using SPSS. The results of this study indicate that tax avoidance as measured by the Effective Tax Rate and Effective Tax Rate has no effect on firm value. Based on the results of the coefficient of determination obtained, it shows that there are other variables outside of this study that can affect firm value. K eywords : Book Tax Difference, Effective Tax Rate, Firm Value , Price Book Value , Tax Avoidance